FluxProg 2.0 - Teaching Introductory Programming Using Flowcharts with Real and Simulated Robots for The Brazilian Robotics Olympiad (OBR) - Fabro, João Alberto; Gutierrez, Matheus Biscaya; Caetano, Fernando Henrique Ratusznei (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2022: Anais do XIV Simpósio Brasileiro de Robótica e XIX Simpósio Latino Americano de Robótica, 2022)
In this paper, an approach to aid in introductory programming courses is presented, focused on students that had never had any contact with computer programming. The approach, that was introduced in a previous paper [3], presents programming concepts using icons and “flowcharts”, and a 3D robotics simulator (CoppeliaSim), that has free educational use. This time, a real version of the simulated robot, built using Arduino and cheap, easily obtainable electronic components, is also presented. The programs to control the robot are developed by graphically constructing flowcharts on the visual editor, and then following the execution of programs using the simulated (or real) robot, step by step. This graphic program editor is named “FluxProg”, and its 2nd version is now available online, with new features comprising variables, arithmetic and logic expressions, thus providing a complete programming environment.